2017
DOI: 10.1519/jsc.0000000000001916
|View full text |Cite
|
Sign up to set email alerts
|

Can Resistance Training Enhance the Rapid Force Development in Unloaded Dynamic Isoinertial Multi-Joint Movements? A Systematic Review

Abstract: Van Hooren, B, Bosch, F, and Meijer, K. Can resistance training enhance the rapid force development in unloaded dynamic isoinertial multi-joint movements? A systematic review. J Strength Cond Res 31(8): 2324-2337, 2017-The objectives of this systematic review were to (a) evaluate whether resistance training can improve the rapid force development in unloaded dynamic isoinertial multi-joint movements and (b) investigate whether these effects differ between untrained/recreationally trained and well-trained indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 71 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…In accordance with the modified scale [ 34 , 35 ], the scores of 14 included articles ranged from 12 to 18, the mean score was 15. Therefore, the overall quality was moderate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the modified scale [ 34 , 35 ], the scores of 14 included articles ranged from 12 to 18, the mean score was 15. Therefore, the overall quality was moderate.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the most risk of bias assessment scales such as Delphi scale, PEDro scale and Cochrane scale are designed for medical research, studies about training interventions usually get very low score under these methodological scales [ 34 ]. We preferred the scale ( Table 1 ) modified by Brughelli et al [ 34 ] and Hooren et al [ 35 ]. This scale is deemed more suitable for sport science research, and includes 10 items, with each item rated as: 0 = clearly no/not reported, 1 = maybe, and 2 = clearly yes.…”
Section: Methodsmentioning
confidence: 99%
“…Given lots of risk of bias assessment scales (Cochrane scale, Delphi scale, Pedro scale) are specialized for medical research, trials in sport science usually were evaluated as poor quality in accordance with these methodological scales [ 23 ]. We chose the scale ( S2 Table ) modified by Brughelli et al [ 23 ] and Hooren et al [ 24 ]. This scale is deemed more suitable for sport science research, and includes 10 items, with each item rated as: 0 = clearly no/not reported, 1 = maybe, and 2 = clearly yes.…”
Section: Methodsmentioning
confidence: 99%
“…Previous evidence shows that multi-joint exercises (squat, leg press, etc.) improve intra-and inter-muscular coordination to a greater extent than single-joint exercises [36]. Therefore, it is presumable that multi-joint exercises could have a greater impact on balance.…”
Section: Discussionmentioning
confidence: 99%